2020
DOI: 10.1111/josh.12948
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Engaged Approach to the Development and Implementation of a Student‐Centered Return to Learn Care Plan After Concussion

Abstract: BACKGROUND: Current return to learn (RTL) after concussion guidelines lack specificity for individualized student care, limiting potential for adoption and implementation. We used a community-engaged research framework to develop and evaluate the implementation of a student-centered care plan that assists school personnel in facilitating RTL. METHODS: We used best-practice RTL guidelines and input from administrators and medical experts to iteratively develop a flexible student-centered care plan. Thirteen sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This study aimed to better understand concussion symptoms and need for temporary accommodations. Using a four week school-based student centered RTL care plan (Conrick et al, 2020), we found that: 1) many students who reported a concussion to school had a history of prior concussion and depression, 2) most students experienced concussion symptoms beyond two weeks, 3) students in the long symptom duration group had more symptoms and more severe symptoms during the first week of reporting compared to students whose symptoms resolved within 1-2 weeks from RTL care plan start, 4) RTL coordinators recommended corresponding temporary accommodations for reported symptoms across all domains in the majority of cases, and 5) RTL coordinators least often recommended corresponding accommodations for sleep symptoms. In combination, these data collected and provided by school staff suggest that students who reported concussion symptoms to schools needed and received many student-centered temporary accommodations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study aimed to better understand concussion symptoms and need for temporary accommodations. Using a four week school-based student centered RTL care plan (Conrick et al, 2020), we found that: 1) many students who reported a concussion to school had a history of prior concussion and depression, 2) most students experienced concussion symptoms beyond two weeks, 3) students in the long symptom duration group had more symptoms and more severe symptoms during the first week of reporting compared to students whose symptoms resolved within 1-2 weeks from RTL care plan start, 4) RTL coordinators recommended corresponding temporary accommodations for reported symptoms across all domains in the majority of cases, and 5) RTL coordinators least often recommended corresponding accommodations for sleep symptoms. In combination, these data collected and provided by school staff suggest that students who reported concussion symptoms to schools needed and received many student-centered temporary accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Students who were diagnosed with concussion by a health care provider and reported it to the school, regardless of whether the concussion took place at school or elsewhere, were eligible to receive the RTL care plan by the school. Feasibility and acceptability of the RTL care plan by 13 public high schools were previously reported (Conrick et al, 2020). Five of these 13 Seattle public high schools detailed information on symptoms and corresponding temporary accommodations.…”
Section: Schools and Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the current national spotlight on student health during the coronavirus pandemic, educators have an opportunity to push forward an agenda focused on improving SRC protocols. Therefore, the following specific recommendations are offered for student health educators based on the findings of this systematic review: Use established, current, research‐based concussion education guidelines, such as the CDC's Heads Up 13 ; Investigate alternative delivery methods, such as electronic or app‐based media, to entice adolescents to actively participate in concussion education; Develop educational interventions designed specifically for at‐risk populations, including girls, programs without athletic trainers, and athletes whose primary language is not English 50 ; Incorporate concussion prevention into health education class curricula as a method of reaching all students 54 ; Actively involve parents in concussion education through school functions, community programs, and social media; Ensure all schools (public and private) develop concussion surveillance protocols to track incidents and help prevent secondary concussions in athletes that are still recovering 55 ; Utilize school nurses as a resource in managing the treatment course and advocating for the appropriate restrictions required for recovery; Individualize RTP and/or return‐to‐learn (RTL) plans based on an athlete's injury and recovery progression, in collaboration with medical systems 56,57 ; Advocate for state Departments of Education to endorse appropriate and researched RTL and RTP protocols with demonstrated successful outcomes 58 …”
Section: Implications For School Healthmentioning
confidence: 99%
“…Strong coordination of care that includes the educational setting as a key partner can help ensure efficient and effective services, including an adaptation of the learning environment in a way that accommodates physical, cognitive, and emotional needs 27 . This includes coordinating with school‐based‐related service providers who are allied health professionals, such as speech pathologists, occupational therapists, and physical therapists 28 . Although there is expert opinion literature on improving educational services for children with TBIs, 29‐31 as well as a small number of studies examining issues related to hospital‐school transition and school reintegration, 32‐34 few empirical studies specifically examine care coordination between medical and educational providers for students with TBIs.…”
mentioning
confidence: 99%